Sequences Analysis of ITS Region and 18S rDNA of Ulva. (10th May 2011) - Lin, Zijie; Lin, Zhongheng; Li, Huihui; Shen, Songdong
Abstract : Ulva, as the main genera involved in green tides in the Yellow Sea, has attracted serious concern in China. Especially, Ulva prolifera is one of the causative species of the occurring. This paper focused on the complete sequences analyses of ITS, 18S, and the combined data to determine phylogenetic relationships among taxa currently attributed to Ulva, Monostroma, and some other green algal. The samples are all concluded in the area of Yellow Sea, China. The results showed the content of G+C in 18S was approximately concentrated upon 49% in average of 19 subjects while the ITS region content of base G and C is obviously higher than A and T. Comparing the ITS and 18S rDNA sequences obtained in this paper to other species retrieved from GenBank, the genetic distance and the ratio of sequence divergence reflect that U. pertusa and U. prolifera had closer genetic relationship with an 18S rDNA, which had genetic distance of 0.007 while ITS had further genetic distance. According to further comparison, Ulva prolifera has closest genetic distance with Chloropelta caespitosa (0.057) and Ulva californica (0.057), which is a reverification coincided Chloropelta, Enteromorpha, and Ulva are not distinct genera.